Tundra Fires and Two Archaeological Sites in the Seward Peninsula, Alaska - Racine, Charles H.; Racine, Marilyn M. (ARCTIC, 1979)
A 1977 tundra fire in the Seward Peninsula, Alaska removed the vegetation mats surrounding and covering several stone-lined pits and a cache pit near the east shore of Imuruk Lake. Bones and artifacts which had been covered by and incorporated into these vegetation mats were strikingly revealed in situ. None of these objects were found during a brief reconnaissance of these sites by the author and others in 1973. These observations supplement the original interpretation of the sites and suggest benefits from locating and examining archeological sites in areas of relatively recent tundra fire.